Values for public service: lessons learned from recent trends and the millennium summit - Argyriades, Demetrios (2003)
This article was originally prepared for circulation at the Second Specialized International Conference of the IIAS, which took place in New Delhi from 5 to 9 November 2002. It was presented orally, in a much abridged form, in the context of the Workshop on Relations between International Organizations and National Administrations in Sustainable development Policies. As the title suggests, the article's point of departure is the Millennium Summit (September 2000) and the sequence of events which have followed and are still unfolding. The Milennium Declaration and the logic of the events of the past two years bring into sharp relief the salience of good governance and of public service values, in this context. They also, one could argue, cast doubt on the validity of managerial doctrines which held sway in the 1980s and 1990s and undermined these values. The market model of government assiduously pursued the shrinkage of the state and the devaluation of public service. It questioned the identity of public administration and promoted the idea that governments should follow and adopt not only the methods and practices but also the values of business. Efficiency and effectiveness ranked at the top of those values. Regulations and rules were discounted. `Results' were enjoined over `process' In retrospect, the outcomes of this approach have proved very uneven and mixed. Experience demonstrates the need for some degree of of separation between the world of business and that of government, between the private sector and the public sphere. Some boundaries are necessary in order to emphasize their separate identities, enhance public service professionalism, reinforce a public service ethic and restore public trust in government. More than anything else, a degree of separation is needed to preserve and to sustain integrity, commitment, objectivity and independence, which must be seen as the marks of the true professional. - Reproduced.
Keywords: Public administration